2005
DOI: 10.1182/blood-2004-08-3238
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive mobilization of CD34+ cells into the peripheral blood in idiopathic myelofibrosis may be due to the action of a number of proteases

Abstract: Idiopathic myelofibrosis (IM) is characterized by increased numbers of CD34

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 50 publications
(70 reference statements)
5
106
0
4
Order By: Relevance
“…It has been suggested that it may be due to increased cleavage of the extracellular domain of CXCR4 because of the proteolytic environment created by the pathological neutrophil emperipolesis within the megakaryocytes 15 . In this context, the normal levels of CXCR4 expressed by the megakaryocytes present in the marrow of Gata1 low mice are of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that it may be due to increased cleavage of the extracellular domain of CXCR4 because of the proteolytic environment created by the pathological neutrophil emperipolesis within the megakaryocytes 15 . In this context, the normal levels of CXCR4 expressed by the megakaryocytes present in the marrow of Gata1 low mice are of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, anatomical abnormalities may not be sufficient to alter the balance of events that result in the retention of stem/progenitor cells within the marrow. Other parameters, such as changes in chemokine levels 10,[12][13][14] and/or disruption of adhesive interactions favoring retention of stem/progenitor cells within the marrow 15 , may be operational.…”
Section: Introductionmentioning
confidence: 99%
“…15,18 The percentage of cells migrating was calculated by determining the ratio of the number of cells recovered from the lower compartment to the total number of cells loaded in the upper compartment. Migrating cells were also assayed in semisolid media for their ability to form hematopoietic colonies and those colonies were plucked and their JAK2 status determined.…”
Section: Migration Assaymentioning
confidence: 99%
“…104 The release of CD34( þ ) cells is generally due to a combination of increased levels of proteases 105 and especially due to the downregulation of the CXCR4 receptor on CD34( þ ) cells. 106 An altered SDF-1/CXCR4 axis was demonstrated in PMF patients with CD34( þ ) cells in the periphery.…”
Section: Spotlightmentioning
confidence: 99%